Circular RNA CCDC66 targets DCX to regulate cell proliferation and migration by sponging miR‐488‐3p in Hirschsprung's disease. Issue 7 (15th November 2018) - Wen, Zechao; Shen, Qiyang; Zhang, Hua; Su, Yang; Zhu, Zhongxian; Chen, Guanglin; Peng, Lei; Li, Hongxing; Du, Chunxia; Xie, Hua; Xu, Xiaoqun; Tang, Weibing
Abstract: It has been suggested that circular RNAs play critical roles in natural growth and disease development. Nevertheless, whether the circular RNAs were related in Hirschsprung's disease (HSCR) remains unknown. Thus, we discovered the cir‐CCDC66 was downregulated in HSCR compared with the normal gut tissues. The cir‐CCDC66 reduction might inhibit cells' proliferation and migration in vitro. Then, we found that DCX transcript was putative cir‐CCDC66 competing endogenous RNA. Furthermore, the function of cir‐CCDC66 as a sponge for miR‐488‐3p to regulate DCX RNA expression was demonstrated by immunoprecipitation and luciferase reporter assays. In conclusion, this is the first report revealing that cir‐CCDC66 modulates DCX expression through sponging miR‐488‐3p and thus participates in the onset of HSCR. Abstract : Circular RNA CCDC66 modulates DCX expression through sponging miR‐488‐3p to regulate cell proliferation and migration in Hirschsprung's disease.